Assessment of three triage systems by medical undergraduate students using simulated disaster patients: a comparative study - Zhang, Jieqiong; Liu, Kui; Chen, Ruilin; Ren, Jie; Wang, Rui; Li, Linyi; Jiang, Jun; Hua, Yan; Wan, Yi (Frontiers in Disaster and Emergency Medicine, 2023)
Triage is an initial important step in emergency medical rescues for mass casualty incidents, and different triage systems are used in practice. However, quantitative analysis-based evidence comparing these triage systems in mass casualty incidents is limited.Objective To compare the performance of three triage systems, simple triage and rapid treatment (START), abbreviated scoring method for combat casualty (ASMcc), and sort assess lifesaving interventions treatment/transport (SALT) system, for simulated disaster patients, as assessed by medical undergraduate students. Methods Medical undergraduates were recruited and randomly divided into three groups to evaluate the performance of the three triage systems by using simulated disaster patient cards. The triage time, accuracy, and overtriage and undertriage rates were analyzed among groups. Furthermore, a questionnaire survey was used to investigate the responses of the participants regarding learning, practice, and satisfaction among the three triage systems.Results A total of 30 participants were included in the study. The participants were male medical undergraduate students with a mean age of 20.73±0.45 years. ASMcc had the highest accuracy of 75% with the lowest over-triage rate of 20%, SALT had the lowest undertriage rate of 19%, and START had the shortest triage time of 12.68±4.96 min (all P<0.05). Furthermore, the results of the questionnaire survey showed that START was easy to learn and recall with high efficiency and, among the three systems, had the highest satisfaction ratings from the participants.The results of the study showed that the three triage systems had their own characteristics and advantages, and they are all suitable for use in mass casualty incidents. Further studies involving more triage systems with data based on real conditions are recommended.